Analisis Cost-Volume-Profit sebagai Alat Bantu Perencanaan Laba pada CV. Obor Inti Boga Jember - Fajar Dwi Safitri; Norita Citra Yiarti; Elok Fitriya (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Cost Volume Profit is one method that can help MSMEs to make the desired profit planning by considering many aspects, starting from the contribution margin, safety margin, breakeven point and operating leverage. This makes a separation between variable costs and fixed costs in the company, so that the company is safer in planning profits as expected. CV. The Boga Core Torch is one of the objects used in this research, because during the pandemic CV. Torch Inti Boga experienced a fluctuating turnover, thus affecting the company's profit. So that the results of the CVP research on CV. Boga Inti Torch is an expected profit of 15% of sales, which means Rp. 1.554.458.831, with sales to be achieved of Rp. 5.056.329.688 with a quantity to be sold of 88.000.864 Kw.